The Distribution of Target Ownership and the Division of Gains in Successful Takeovers - Stulz, Rene M.; Walkling, Ralph A.; Song, Moon H. (Journal of Finance, 1990)
This paper presents evidence that the distribution of target ownership is related to the division of the takeover gain between the target and the bidder for a sample of successful tender offers. In the whole sample, the target's gain is negatively related to bidder and institutional ownership. In the sample of multiple-bidder contests, the target's gain increases with managerial ownership and falls with institutional ownership.